Quintuplet Pregnancy in a women with HIV positive status - Neupane, Bibhushan; Chaudhary, Babita; Bam, Shiba (Nepal Journal of Obstetrics and Gynaecology, 2021)
Quintuplets are a rare occurrence and even rarer if they are born to a woman without fertility treatment. It is associated with not only high rates of obstetric complications but also increased perinatal morbidity and mortality. We here report a case of a woman with HIV positive status under ART with Quintuplets who delivered on her second trimester.